Cover Feature: Direct Synthesis of Ammonia from N2 and H2O on Different Iron Species Supported on Carbon Nanotubes using a Gas‐Phase Electrocatalytic Flow Reactor (ChemElectroChem 14/2020). Issue 14 (17th June 2020) - Chen, Shiming; Perathoner, Siglinda; Ampelli, Claudio; Wei, Hua; Abate, Salvatore; Zhang, Bingsen; Centi, Gabriele
Abstract : The Cover Feature illustrates that the active species in N2 reduction to ammonia are small iron‐oxide species supported on carbon nanotubes. More information can be found in the Article by S. Chen et al .